1991
DOI: 10.1111/j.1365-2141.1991.tb08063.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of human, rat and mouse erythropoietins by isoelectric focusing: differences between serum and urinary erythropoietins

Abstract: Isoelectric focusing (IEF) in the pH range 2.5-5.0 has been used to compare the immunoreactive (ir) erythropoietin (Epo) in paired samples of serum and urine from three patients, two with idiopathic aplastic anaemia and one with paroxysmal nocturnal haemoglobinuria and also from three anaemic rats. Serum samples only were also examined from two further patients with aplastic anaemia and from three mice, made anaemic (like the rats) by irradiation and phenylhydrazine treatment. Most of the ir-Epo recovered afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…15,26,52,55,73,74 Tam et al 55 analyzed serum from anemic patients by IEF demonstrating charge patterns similar to those in the current study, whereas Sohmiya and Kato 74 recently showed that normal human serum after IEF contained 4 more basic forms of EPO. Although these discrepancies could be attributed to the pathologic conditions of the patients, they may also reflect variations within or between healthy persons.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…15,26,52,55,73,74 Tam et al 55 analyzed serum from anemic patients by IEF demonstrating charge patterns similar to those in the current study, whereas Sohmiya and Kato 74 recently showed that normal human serum after IEF contained 4 more basic forms of EPO. Although these discrepancies could be attributed to the pathologic conditions of the patients, they may also reflect variations within or between healthy persons.…”
Section: Discussionsupporting
confidence: 74%
“…Several reports on endogenous hEPO have shown that circulating hEPO contains fewer acidic glycoforms than urinary hEPO. 55,57 Wide et al 57 also showed that rhEPO secreted in the urine is more acidic than rhEPO analyzed from serum of the same subject and concluded that the charge difference could be attributed to a difference in renal handling of the various glycoforms of hEPO, indicating a reabsorption of certain glycoforms. Several studies 15,60,81 have demonstrated that the apparent molecular weight of purified urinary hEPO on SDS-PAGE is similar to that of rhEPO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The isoform composition of a particular preparation of EPO depends on its source. Thus, in the case of endogenous human EPO, differences have been found between the isoform compositions of serum and urinary EPO (Tam et al, 1991;Wide et al, 1995), and between serum EPO obtained from subjects under different physiological conditions (Wide & Bengtsson, 1990). In the case of rEPO, the isoform composition is influenced by the cell line and culture conditions used for its synthesis, and the selectivity of the purification procedures used to isolate the preparation.…”
mentioning
confidence: 99%
“…Like other glycoprotein hormones, EPO exists as mixtures of a multitude of isoforms, differing mainly in their glycosylation (Storring, 1992). The isoform composition of EPO preparations varies with their source, differing between samples from serum and urine (Tam et al, 1991;Wide et al, 1995), between samples obtained from subjects under different pathophysiological conditions (Wide & Bengtsson, 1990), and between human urinary EPOs and different recombinant DNA-derived human EPOs (rEPOs) (Storring & Gaines Das, 1992;Storring et al, 1996). This is because glycosylation of the polypeptide moiety of a glycoprotein such as EPO is a post-translational process which is influenced by the type of cell in which the EPO is synthesized and the physiological factors, including culture conditions, acting upon this cell (Rademacher et al, 1988;Cumming, 1991).…”
mentioning
confidence: 99%